Prospective study into the incidence of Lambert Eaton myasthenic syndrome in small cell lung cancer. - Payne, M; Bradbury, P; Lang, B; Vincent, A; Han, C; Newsom-Davis, J; Talbot, D (2010)
INTRODUCTION: The Lambert Eaton myasthenic syndrome (LEMS) is a paraneoplastic disorder associated with raised serum voltage-gated calcium channel (VGCC) antibodies in patients with small cell lung cancer (SCLC). VGCC can also be found in patients with SCLC and cerebellar ataxia. This was a prospective study to assess the incidence of clinical and subclinical LEMS or other neurologic disease in patients with SCLC. PATIENTS AND METHODS: Sixty-three unselected patients with cytologically or histologically confirmed SCLC consented to participate. Pretreatment assessment included a neurologic symptom questionnaire, examination for physical signs of LEMS or ataxia, measurement of serum titers of antibodies to P/Q-type VGCCs by radioimmunoassay in all patients and electrophysiological examination where appropriate. RESULTS: Neurologic symptoms unrelated to LEMS occurred in 26% of patients. Five patients (8%) had raised serum VGCC antibodies (range, 69-1553 pM/l) diagnostic of LEMS, two (3%) of whom had LEMS on clinical and electrophysiological grounds. Both also had mild cerebellar ataxia. There was no association between serum VGCC antibody titer and survival. CONCLUSION: Routine measurement of VGCC antibodies in patients without clinical LEMS is unlikely to assist either in management of SCLC or in assessment of prognosis.